Ethnographic Research on the Impact of COVID-19 on Families with Older Adults Residing on Remote Islands in Japan: Directed Content Analysis Based on the Concentric Sphere Family Environment Theory - Hohashi, Naohiro; Pinyo, Jaroensuk; Araki, Shiho; Taniguchi, Minami (Al-Hijrah Indonesia, 2023)
Coronavirus disease 2019 (COVID-19) impacts not only on the health of individuals, but also on family functioning and a family’s well-being. Japan’s remote outer islands, with their aging populations, harbor a unique culture, and it is believed that the COVID-19 pandemic has impacted on such populations in a distinct manner. This study aims to clarify the impacts of COVID-19 on families with older adults residing on remote islands, using the Concentric Sphere Family Environment Theory (CSFET) as a theoretical framework. We conducted family ethnographic research including semi-structured interviews with 14 families on Japanese islands whose total population numbers approximately 34,000, and performed directed content analysis of impacts on the families using CSFET. Forty-three categories were extracted according to the five systems of the CSFET. For example, negative impacts such as “occurrence of concerns over the scarcity of medical institutions” in the macro system; positive impacts such as “growing consideration of the life span of older adult family members” in the chrono system; and context-sensitive impacts such as “changes in family’s awareness of infections arising from the contents of information on infectious diseases” in the macro system were identified. The islands’ characteristics, such as vulnerabilities in terms of medical care, isolated environment and strong community ties, were considered as impacting both within and outside of the family. Accordingly families with older adults experienced negative impacts, but also found positive impacts in their difficulties.